Pengembangan Keterampilan Hard Skill Siswa Melalui Pelatihan Microsoft Excel di SMKS Al Muhajirin Arosbaya - Putri, Aurellia Maharani (Unity Academy, 2024)
Microsoft Excel training at SMKS Al-Muhajirin arosbaya focuses on the importance of hard skills in the world of education and work, especially in the digital era and evolving technology. Mastery of microsoft excel is a skill that is needed in various sectors, especially in the field of administration and finance. Based on the results of the pre-test conducted on students of Class X TKJ SMKS Al-Muhajirin their Microsoft Excel skills are still very lacking, with the majority of students are in the category of